Correction: Introduction of a mediator for enhancing photocatalytic performance via post-synthetic metal exchange in metal–organic frameworks (MOFs). Issue 53 (7th July 2015) - Sun, Dengrong; Liu, Wenjun; Qiu, Mei; Zhang, Yongfan; Li, Zhaohui
<x xml:space="preserve">Abstract</x> Correction for 'Introduction of a mediator for enhancing photocatalytic performance via post-synthetic metal exchange in metal–organic frameworks (MOFs)' by Dengrong Sun et al., Chem. Commun., 2015, 51, 2056–2059.